Imaginario burgués y arquitectura teatral en la España del siglo diecinueve - Peruarena Arregui, Juan; Profesor Universidad de Valladolid, España (Pontificia Universidad Javeriana, Bogotá, 2005)
The nineteenth century theatre–building, as a whole, is revealed like an standard, designed in such a way that satisfy a social group’s practical or symbolic needs: the mentality or ideological imaginary shared by the heterogeneous group known as middle–class, identified in general terms by the category of “bourgeoisie.” Among the most neglected aspects by the nineteenth century historiography dedicated to theatre design, there are certain categories like the economic and social benefit, the security, the comfort, the ornamentation of the ambiences or the increasing interest on the functional accessories from the building which are verified in the equipment of those facilities assigned to social life, that becomes one of the basic functions of eighteenth century theatre. Based on these ideas, the theatre morphology that will prevail in nineteenth century hols a specific personality in which two aspects take part. In one hand, a long solidly maintained tradition trough the historic evolution; by the other, the transformations that the building has suffered because of all the circumstances referred, not only to drastic structural or formal innovations, but also to the peculiar ethic and technique idiosyncrasy and the renegotiation of uses and meanings all imposed by its adaptation to the socio–cultural requirements within contemporary times.